Evaluation of the Monark Wingate Ergometer by direct measurement of resistance and velocity - MacIntosh, B. R.; Bryan, S. N.; Rishaug, P.; Norris, S. R. (Canadian Journal of Applied Physiology, 2001)
The purpose of this study was to assess the accuracy of the new basket-loaded Wingate ergometer introduced by Monark (Model 834E). Velocity was measured directly from the pedal switch while tension was measured with transducers on each end of the brake lacing. Moment of inertia of the flywheel was determined and accounted for in the calculation of power. Constant load tests (39.24 to 98.1 N), were done at pedaling speeds from 80 to 140 r \mult\min-1 (flywheel angular velocity = 30-50 rad \mult\ s-1). The load transmitted to the lacing at the front and back of the flywheel was 95.5 ± 0.8% (mean ± SEM) and 6.71 ± 0.8%, respectively, of the load in the basket. Thus, the resultant tension (front minus back) was on average 88.8 ± 0.57% of the applied load. The velocity recorded by the Monark Wingate Ergometer computer program (MWECP) was the same (100.4 ± 1.56%) as that determined from the pedal switch directly. Five male mountain bikers performed a 30-s all-out test. Peak power calculated by MWECP (1181 ± 55W) was always higher (p < .01) than that calculated from direct measures of tension and velocity (1102 ± 66W), when not taking into account the moment of inertia. These experiments suggest that the basket-loaded Monark Wingate ergometer does not provide a correct calculation of power because of incomplete load transmission to the flywheel.